CLINICAL AND METHODOLOGICAL BASIS OF HEMODYNAMIC DISORDERS AND PEDIATRIC DIAGNOSTICS IN CONGENITAL HEART DEFECTS - Rakhimova Mashhura Shahobiddinovna; Turdiyev Shuhrat Berdiyevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This scientific article presents a clinical-methodological analysis of congenital heart defects (CHDs), focusing on hemodynamic disorders in Tetralogy of Fallot, ventricular septal defect (VSD), and atrial septal defect (ASD). Based on the principles of propedeutic pediatrics, the work explains the mechanisms of left-to-right and right-to-left shunts, the role of teratogenic and genetic factors in antenatal morphogenesis, and the diagnostic value of echocardiography as the “gold standard”. The article emphasizes the pediatrician’s role in early detection during infancy. Key pathophysiological changes – cardiomegaly, “drumstick” fingers, and pathological murmurs – are discussed in detail.